PENGARUH LIABILITAS PAJAK TANGGUHAN, UKURAN PERUSAHAAN, DAN KONSENTRASI KEPEMILIKAN TERHADAP EARNINGS MANAGEMENT (Studi Empiris pada Perusahaan yang Konsisten Terdaftar di LQ45 Tahun 2017-2019) - Nelza, Audea Briliana; Purwanto, Agus (Diponegoro Journal of Accounting, 2022)
The purpose of this research is to know how deferred tax liabilities, firm size, ownership concentration affect earnings management to avoid earnings decline. Earnings management is an activity of manipulating earning information in the financial statements performed by corporate managers with the aim to protect the interests of the company.Population in this study are companies that is consistently included in LQ45 and listed on the Indonesia Stock Exchange during the period 2017-2019. Sample was obtained by using purposive sampling method based on certain criteria. The method of analysis used in this research is multiple regression analysis.The result of multiple regression analysis shows that deferred tax liabilities variable have no significant effect to earnings management. These results prove that there is no effect of the higher company’s deferred tax liabilities cause the greater possibility of the company's earnings management action. On the other hand, firm size and ownership concentration variable have a significant negative effect to earnings management. This indicates that the larger firm size or ownership concentration cause the possibility of companies in the earnings management is getting smaller.